Work-life Balance, Keselamatan dan Kesehatan Kerja (K3), dan Turnover Intention: Studi pada PT Rakyat Makmur Nusantara - Satria, Mohammad Fariz; Dwiatmadja, Christantius (Universitas Proklamasi 45, 2024)
The research aims to test the influence of Occupational Safety and Health (K3) and work-life balance (WLB) on turnover intentions among millennial employees at PT Rakyat Makmur Nusantara. Sampling in this study used a purposive sampling technique where a sample size of 103 respondents was obtained. The analysis technique used in this research is multiple linear regression. Based on the research that has been conducted, it can be concluded that work-life balance has a negative influence on turnover intention, while K3 has a positive influence on turnover intention.